Pengaruh Gaya Kepemimpinan dan Budaya Organisasi terhadap Komitmen Organisasi dan Kinerja Karyawan di Hotel Rà Suites Simatupang - Tumakaka, Rian Klaudius; Cyasmoro, Verry (Jurnal EMT KITA, 2024)
This study aims to explore the influence of Leadership Style and Organizational Culture on Organizational Commitment and Employee Performance at Hotel Ra Suites Simatupang. The analysis method used is quantitative by distributing questionnaires to 103 employees at Ra Suites Simatupang Hotel, with results dominated by female respondents, 54 people (52.4%), while male respondents were 49 people (47.6%). The marital status of respondents showed 58 married (56.3%) and 45 unmarried (43.7%). The age of the group of respondents was as follows: under 30 years old, 36 people (35%); 31-40 years old, 29 people (28.1%); 41-50 years old, 34 people (33%); over 50 years old, 4 people (3.9%). For the education level of respondents, 14 people (13.6%) were high school graduates, 47 people (45.7%) held diplomas, 39 people (37.8%) had a bachelor's degree, and 3 people (2.9%) had a master's degree. Regarding employment status, 8 people (7.8%) were permanent employees, 58 people (56.3%) were contract employees, 28 people (27.2%) were paid interns, and 9 people (8.7%) were daily workers. Based on the length of employment, 3 people (2.9%) had worked for less than a year, 38 people (36.9%) for 1-2 years, 21 people (20.4%) for 2-3 years, and 41 people (39.8%) for more than 3 years. The last, regarding respondents' domicile, showed that 55 people (53.4%) were from DKI Jakarta, 32 people (31.1%) from Bodetabek, and 16 people (15.5%) from outside Jabodetabek. The data processing results using SmartPLS showed that no indicator had an outer loading value lower than 0.5. Therefore, all indicators with values above 0.5 were suiTabel for further research. The Q-Square (Q²) value obtained for Employee Performance was 0.498 and for Organizational Commitment, it was 0.364. Based on these results, it can be concluded that Organizational Culture and Leadership Style have a significant and relevant influence on these variables